Spatio-temporal dynamics of predatory arthropods in Soybean ecosystems and their relationship with climatic variables - Meena, Narendra; Bhamare, V K; More, D G (Indian Journal of Plant Protection, 2025)
A field investigation was conducted during the Kharif and Rabi seasons of 2024–25 at the Department of Entomology, College of Agriculture, VNMKV, Latur, Maharashtra, to study the spatiotemporal dynamics of predatory arthropods in soybean ecosystems and their relationship with weather parameters. The experiment was carried out under pesticide-free conditions using the soybean variety MAUS 725. Weekly observations of two key natural enemies viz., ladybird beetles and spiders were recorded throughout the seasons. Sampling involved randomly selecting five plants from each of three quadrats, across a total of forty-eight quadrats. On Kharif soybean, ladybird beetle populations ranged from 0.50 to 3.67 insects per plant, while spider populations varied from 0.10 to 2.70 insects per plant. In the Rabi season, ladybird beetle populations ranged between 0.16 and 2.63 insects per plant, and spiders ranged from 0.12 to 0.83 insects per plant. The peak population of ladybird beetles on Kharif soybean (3.67 insects/plant) was observed in the 37th Standard Meteorological Week (SMW), while spiders peaked (2.70 insects/plant) in the 35th SMW. In Rabi soybean, the highest ladybird beetle count (2.63 insects/plant) occurred in the 47th SMW, and the maximum spider population (0.83 insects/plant) was recorded in the 48th SMW. Correlation analysis revealed that ladybird beetles were positively, though non-significantly, correlated with rainfall and temperature, while spiders showed similar trends, except for a significant negative correlation with afternoon relative humidity during the Rabi season. The peak activity of both predators was higher during the Kharif season, coinciding with moderate to high rainfall, elevated temperatures, and lower afternoon humidity. Statistical analysis confirmed that seasonal weather variations significantly influenced predator populations. These findings underscore the importance of climatic factors in shaping natural enemy dynamics and reinforce the potential role of these predators in integrated pest management strategies under varying seasonal conditions.